2020
DOI: 10.1029/2020jc016455
|View full text |Cite
|
Sign up to set email alerts
|

Shelfbreak Jet Structure and Variability off New Jersey Using Ship of Opportunity Data From the CMV Oleander

Abstract: Repeat measurements of velocity and temperature profiles from the Container Motor Vessel (CMV) Oleander provide an unprecedented look into the variability on the New Jersey Shelf and upper continental slope. Here 1362 acoustic Doppler current profiler (ADCP) velocity sections collected between 1994 and 2018 are analyzed in both Eulerian and stream coordinate reference frames to characterize the mean structure of the Shelfbreak Jet, as well as its seasonal to decadal variability. The Eulerian mean Shelfbreak Je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…Since 1977, XBTs have been deployed from the container ship CMV Oleander on its repeat track from Elizabeth, New Jersey to Hamilton, Bermuda 29 , providing a unique long-term dataset. To investigate the sub-surface expression (vertical structure of water temperature) of the MHW on the southern shelf and slope, we use the monthly XBT gridded temperature sections from the Oleander Line, described in Forsyth et al 13 . These transects span the New Jersey shelf to the northern edge of the Gulf Stream from 1977 to 2018, and temperature anomalies relative to a monthly climatology are reported on a 10-km (cross-shelf) by 5 m (vertical) grid 30 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1977, XBTs have been deployed from the container ship CMV Oleander on its repeat track from Elizabeth, New Jersey to Hamilton, Bermuda 29 , providing a unique long-term dataset. To investigate the sub-surface expression (vertical structure of water temperature) of the MHW on the southern shelf and slope, we use the monthly XBT gridded temperature sections from the Oleander Line, described in Forsyth et al 13 . These transects span the New Jersey shelf to the northern edge of the Gulf Stream from 1977 to 2018, and temperature anomalies relative to a monthly climatology are reported on a 10-km (cross-shelf) by 5 m (vertical) grid 30 .…”
Section: Methodsmentioning
confidence: 99%
“…A regime shift in 2000 is associated with a substantial increase in the number of WCRs formed annually from Gulf Stream meander crests 10 . Large amplitude meanders and WCRs can bring warm salty water into close proximity to the continental slope and shelf break 11 , 12 and can affect both the Shelfbreak Jet as well as shelf temperature 13 . Gawarkiewicz et al 14 found that an ocean-driven MHW along the continental shelf of the Mid-Atlantic Bight in 2017 was forced by the presence of a WCR, which resulted in cross-shelf transport of warm and salty Gulf Stream water.…”
Section: Introductionmentioning
confidence: 99%
“…This portion of the southwestward flow is a part of Northwest Atlantic Shelfbreak Current system (Fratantoni and Pickart 2007) between the west coast of Greenland and the Cape Hatteras. The Middle Atlantic Bight section of this currents system is also known as Shelfbreak Jet (e.g., Gawarkiewicz et al 2018; Forsyth et al 2020). Hereafter, part of the Shelfbreak Current system between the Grand Banks and the Great South Channel at the south border of the Gulf of Maine is referred to as the Shelfbreak Current.…”
Section: Figurementioning
confidence: 99%
“…This relationship indicates that the faster and closer a ring is to the shelf break, the more negative (northeast) the along-shelf flow is. Cases when the ring is slow and far from the shelf break tend to have a shelf break velocity that it is more typical of mean shelf break conditions (Forsyth et al, 2020). It is important to note that and are not correlated with one another (despite each one's correlation with flow at the shelf break).…”
Section: Warm Core Ring Impact On Shelf Break Velocitiesmentioning
confidence: 98%
“…and variability off New Jersey using ship of opportunity data from the CMV Oleander This chapter was originally published as Forsyth, J.,Andres, M., & Gawarkiewicz, G. (2020). Shelfbreak Jet structure and variability off New Jersey using ship of opportunity data from the CMV Ole-…”
mentioning
confidence: 99%